The contemporary management of primary urethral carcinoma. (November 2015) - Blick, Christopher; Sahdev, Varun; Mitra, Anita; Nigam, Raj; Muneer, Asif
Primary urethral cancer is a rare malignancy; the most common histological subtype is squamous cell carcinoma. The aetiology of this cancer is similar to penile cancer and the human papilloma virus (HPV) is thought to be an important factor in tumourigenesis. Surgery with or without chemoradiotherapy is the accepted treatment for primary urethral cancer. Current practice supports penile-sparing surgery, to maximise functional and psychological outcomes. We have reviewed the literature to summarise the pathogenesis and management of primary urethral cancer.